Using the Learning Design Language to model activities supported by services. (11th July 2008) - Martel, Christian; Vignollet, Laurence
The main objective of the field of Learning Design (LD) is to provide teachers and instructional designers with the conceptual and technological means to create and manage e-learning activities. This paper addresses a paradox in existing approaches to LD: the activity mediated by services is neither prescribed nor observed. Our proposition is to use LD languages to model an activity supported by a service. This paper describes how to use a specific LD language, also called Learning Design Language (LDL), to model such activities and how Learning Design Infrastructure (LDI), the associated infrastructure, has been extended to allow the operationalisation and execution of these improved scenarios. Thus, the approach attempts to improve service support in the LD field.